Driving Financial Performance In The Digital Era: The Strategic Roles Of Financial Literacy, Fintech, and Financial Inclusion - Rita Kusumawati; Selvia Putri Yasmara (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of financial literacy and financial technology on the financial performance of MSMEs in Yogyakarta, both directly and indirectly through financial inclusion as a mediating variable. The population in this study consists of Micro, Small, and Medium Enterprises (MSMEs) located in the City of Yogyakarta. A quantitative approach was used with a sample of 217 MSME respondents. Data were collected through a questionnaire distributed via Google Form and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy and financial technology have a positive and significant effect on the financial inclusion of MSMEs. Furthermore, financial inclusion also has a positive and significant effect on the financial performance of MSMEs. Financial literacy and financial technology also have a direct positive effect on financial performance. The mediation analysis reveals that financial inclusion can mediate the effect of financial literacy and financial technology on the financial performance of MSMEs. This study can strengthen previous theories regarding the effect of financial literacy and financial technology on financial performance, as well as the role of financial inclusion as a mediating variable. This study has implications for researchers in gaining a deeper understanding of financial practices in the business world, particularly in the MSME sector. The limitations of this study are confined to certain factors, so it has not included other variables that could potentially affect the financial performance of MSMEs, such as financial attitude and financial management.